Assessment of Pulmonary Function Using Spirometry in Patients with Diabetes Mellitus: A Cross-Sectional Comparative Study - Rashid, Mohammad Bazlur; Shahida, Shammi Ara; Mahmud, Rakib Hasan; Ahmed, KM Ahsan; Haque, Md Azizul (Journal of Rangpur Medical College, 2026)
Background: Diabetes mellitus (DM) is a long-term metabolic disease that is becoming more common around the world. Its systemic complications affect more than just the usual target organs. However, pulmonary involvement in diabetes is still not well understood in everyday clinical practice. Objective: To evaluate pulmonary function via spirometry in patients with diabetes mellitus and to investigate the correlation between lung function deterioration and disease duration. Methods: A cross-sectional comparative study was performed from June to November 2013 at Rajshahi Medical College Hospital and Rajshahi Diabetic Association General Hospital in Bangladesh. There were 88 participants who did not smoke and were not obese. They had type 1 DM, type 2 DM, or were matched with non-diabetic controls. Spirometry was used to measure pulmonary function (FVC, FEV_, FEV_/FVC), and SPSS version 16.0 was used to look at the data. Results: Both type 1 and type 2 diabetic patients showed a significant drop in FVC and FEV_ (measured and % predicted) when compared to controls (p<0.01). The FEV_/FVC ratio stayed the same or went up, which means that the breathing pattern was mostly restrictive. Every person with type 1 diabetes and about 78–79% of people with type 2 diabetes had FVC values that were less than 80% of what was expected. A longer duration of diabetes (>10 years) was significantly correlated with greater decreases in FVC and FEV_ (r=−0.48, p=0.002). Conclusion: Diabetes mellitus, especially of extended duration, is linked to considerable restrictive pulmonary dysfunction, underscoring the lungs as a critical target organ in diabetes. J Rang Med Col.2026 Mar;11(1): 51-56